Размножение оленя пятнистого (Cervus nippon hortulorum Sw.) в условиях Среднего Приднепровья - Евтушевский, Н.Н. (Вестник зоологии, 1974)
The rut begins usually in the second half of September and is over in the middle of November. The redundancy of males in the places of the main rut results in acute forms of nuptial duels. The weight and dimensions of embryos are approximately equal to those obtained in the respective months in Primorye. Tht usual time of calving - the end of May-June. The data on the weight and dimensions of 7-9 months old deer testify to their rapid growth. Dying out of young animals is insignificant.